2022
DOI: 10.3390/math11010100
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Analysis and Adaptive Finite-Time Sliding Mode Control Approach of the Financial Fractional-Order Chaotic System

Abstract: In this work, we studied the complex behaviors of the fractional-order financial chaotic system, consisting of a simple, relatively chaotic system with two quadratic nonlinearities (QN) and a sextic nonlinearity (SN). We completed and enriched the results presented in the study of Subartini et al. (2021). As a result of this, our study focused more on the fractional order and adaptive finite-time sliding mode control in the financial risk chaotic system. The dynamical behaviors of the financial chaotic system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…When considering the impact of religion on Muslim tourist destinations, it becomes crucial to ensure that the principles of Islam are integrated into the tourist services provided. This alignment with Islamic requirements can contribute significantly to the satisfaction of tourists (Johansyah et al, 2022). Tourists who have experienced and appreciated Islamic attributes, as highlighted by Battour et al (2014), tend to derive contentment from their travel experiences.…”
Section: Islamic Attributesmentioning
confidence: 94%
“…When considering the impact of religion on Muslim tourist destinations, it becomes crucial to ensure that the principles of Islam are integrated into the tourist services provided. This alignment with Islamic requirements can contribute significantly to the satisfaction of tourists (Johansyah et al, 2022). Tourists who have experienced and appreciated Islamic attributes, as highlighted by Battour et al (2014), tend to derive contentment from their travel experiences.…”
Section: Islamic Attributesmentioning
confidence: 94%
“…The 0-1 test is an efficient method for quantitatively determining the chaotic behavior of a database [40][41][42]. It was proposed by [28,40], and successfully used in systems from different areas of knowledge, including economic and financial systems represented in fractional order [20,21,23,24]. The method consists in determining a parameter, K = [0 : 1].…”
Section: Application Of 0-1 Testmentioning
confidence: 99%
“…Computational results showed that the fractional order influences the system's stability and Hopf bifurcation. In [20], the dynamic analysis of an economic system with chaotic behavior is presented, using an adaptive control by sliding modes in the chaos control. The 0-1 test and the Lyapunov exponent prove the chaotic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…After that, Ahmad et al have developed a new robust nonlinear control strategy for stabilizing a CFS within a finite time, in which the efficiency of the closedloop was improved [34]. In addition, the terminal sliding mode control [35], adaptive control [36], H ∞ control [37], and others [38] have been utilized in CFSs for achieving finite-time stabilization or synchronization.…”
Section: Introductionmentioning
confidence: 99%